Underwater noise pollution as an ecological crime: a global problem in the anthropocene = Unterwasserlärmverschmutzung als ökologisches Verbrechen: ein globales Problem im Anthropozän - Morelle-Hungría, Esteban (Kriminologie - das Online-Journal, 2023)
Noise pollution is recognized globally as a genuine environmental pollutant. Its effects are not limited to just terrestrial ecosystems, they can also affect aquatic environments at different levels. The scientific community has provided ample evidence of this. It is essential that legal systems and environmental protection regulations reflect this understanding. The aim of this study is to analyse the evolution of international legislation concerning noise pollution, as a response by legislative bodies to the environmental impacts it can have. These impacts have been classified on the basis of the ecological studies which are the subject of the analysis. Thus, the possible configuration of some types of noise pollution as criminal is analysed according to the concept of Green Criminology. The ecological damage generated at the different levels of the ecosystem approach is the focus of this analysis. This classifying system could allow us to configure an appropriate criminal response to the effects generated by this polluting activity.